A human FSHB transgene encoding the double N-glycosylation mutant (Asn7Δ Asn24Δ) FSHβ subunit fails to rescue Fshb null mice. (5th May 2016) - Wang, Huizhen; Butnev, Vladimir; Bousfield, George R.; Kumar, T. Rajendra
Abstract: Follicle-stimulating hormone (FSH) is a gonadotrope-derived heterodimeric glycoprotein. Both the common α- and hormone-specific β subunits contain Asn-linked N-glycan chains. Recently, macroheterogeneous FSH glycoforms consisting of β-subunits that differ in N-glycan number were identified in pituitaries of several species and subsequently the recombinant human FSH glycoforms biochemically characterized. Although chemical modification and in vitro site-directed mutagenesis studies defined the roles of N-glycans on gonadotropin subunits, in vivo functional analyses in a whole-animal setting are lacking. Here, we have generated transgenic mice with gonadotrope-specific expression of either an HFSHB WT transgene that encodes human FSHβ WT subunit or an HFSHB dgc transgene that encodes a human FSHβ Asn7Δ 24Δ double N-glycosylation site mutant subunit, and separately introduced these transgenes onto Fshb null background using a genetic rescue strategy. We demonstrate that the human FSHβ Asn7Δ 24Δ double N-glycosylation site mutant subunit, unlike human FSHβ WT subunit, inefficiently combines with the mouse α-subunit in pituitaries of Fshb null mice. FSH dimer containing this mutant FSHβ subunit is inefficiently secreted with very low levels detectable in serum. Fshb null male mice expressing HFSHB dgc transgene are fertile and exhibit testis tubule size and sperm number similar to those of Fshb null mice. Fshb null female mice expressing the mutant, but not WT human FSHβ subunit-containing FSH dimer are infertile, demonstrate no evidence of estrus cycles, and many of the FSH-responsive genes remain suppressed in their ovaries. Thus, HFSHB dgc unlike HFSHB WT transgene does not rescue Fshb null mice. Our genetic approach provides direct in vivo evidence that N-linked glycans on FSHβ subunit are essential for its efficient assembly with the α-subunit to form FSH heterodimer in pituitary. Our studies also reveal that N-glycans on FSHβ subunit are essential for FSH secretion and FSH in vivo bioactivity to regulate gonadal growth and physiology. Highlights: In vivo functions of N-linked glycans on human FSHβ subunit tested in mouse models. HFSHB WT and HFSHB dgc (encodes a N-glycosylation mutant hFSHβ subunit) mice are generated on an Fshb −/− background. HFSHB transgenes are targeted to pituitary and specifically expressed in gonadotropes. HFSHB dgc encoded double N-glycosylation mutant human FSHβ subunit inefficiently assembles with mouse α-subunit. Double N-glycosylation mutant human FSHβ subunit containing FSH dimer is inefficiently secreted and does not rescue Fshb −/− mice.